2004
DOI: 10.1097/01.ccm.0000109776.56410.f1
|View full text |Cite
|
Sign up to set email alerts
|

A lazaroid mitigates postresuscitation myocardial dysfunction

Abstract: The lazaroid compound U-74389G, administered during cardiac arrest, mitigated postresuscitation myocardial dysfunction and improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…100 Zhang et al 25 demonstrated that by inhibiting nitric oxide production with nitric oxide synthase (NOS) inhibitor during a myocardial ischemia-reperfusion sequence, coronary sinus free radical concentration was significantly diminished and accumulation of the peroxynitration product was abolished. Administration of 21-aminosteroids (lazaroids) during CPR has contributed to the improvement of postresuscitation function and better neurologically normal survival.…”
Section: Free Radical Inhibitorsmentioning
confidence: 99%
“…100 Zhang et al 25 demonstrated that by inhibiting nitric oxide production with nitric oxide synthase (NOS) inhibitor during a myocardial ischemia-reperfusion sequence, coronary sinus free radical concentration was significantly diminished and accumulation of the peroxynitration product was abolished. Administration of 21-aminosteroids (lazaroids) during CPR has contributed to the improvement of postresuscitation function and better neurologically normal survival.…”
Section: Free Radical Inhibitorsmentioning
confidence: 99%
“…Ischemia, reperfusion injury, inflammation, and related cytokines, catecholamines, microvascular injury, and defibrillation individually or in combination cause postresuscitation myocardial failure [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been shown, in addition to other therapeutic actions, to improve renal and intestinal blood flow [7,8] in septic shock, and myocardial function in ischemia-reperfusion injury [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%